Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Les dessous des Folles alliées : un livre affriolant - Godbout, Lucie (Les éditions du remue-ménage, 1993)
Lucie Godbout, ex-Folle alliée, rappelle ici dix ans de théâtre, de cabaret, de shows tous plus drôles les uns que les autres… Un livre aussi vivant que leurs spectacles, des personnages qui interviennent dans le récit et des extraits de leur dernier show, C’est parti mon sushi!
https://www.editions-rm.ca/livres/les-dessous-des-folles-alliees-un-livre-affriolant/
Keywords: 1900-1999; 1980-1989; amériques; discipline; femmes* artistes; histoire des femmes*; histoire et politique; militance; périodes historiques; québec; régions géographiques; thématiques; théâtre; travail

La main tranchante du symbole : textes et essais féministes - Bersianik, Louky (Les éditions du remue-ménage, 1990)
Une anthologie au sous-titre explicite qui regroupe des textes écrits essentiellement entre 1980 et 1990, "choisis à cause de leur perspective féministe et" de "leur vision particulière de la symbolique patriarcale" (selon l'auteure, la société patriarcale est "meurtrière, hypocrite et mensongère"). Le regroupement des textes a été réalisé selon divers thèmes couvergents : l'écriture, la langue, la critique (p. 199-221), les nouvelles techniques de reproduction, la mémoire du futur, etc. Quelques textes inédits. Extraits de ##L'Euguélionne##, p. 66-91.
Keywords: amériques; antiféminisme; approches et analyses; cours; discipline; fem1000; histoire et politique; militance; mémoire collective; pratiques féministes; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires